Red Lists and conservation prioritization of plant communities – a methodological framework. Issue 3 (21st January 2014) - Berg, Christian; Abdank, Anja; Isermann, Maike; Jansen, Florian; Timmermann, Tiemo; Dengler, Jürgen; Mucina, Ladislav
Abstract Aims Red Lists of threatened species are a well‐established conservation tool throughout the world. In contrast, Red Lists of ecosystems, habitats or plant community types have only recently found interest at the global level, although they have a longer tradition in Central Europe. We contribute to the debate by presenting and discussing a comprehensive conservation assessment methodology for plant communities that was developed within the framework of the project 'The plant communities of Mecklenburg‐Vorpommern and their vulnerability'. Location Mecklenburg‐Vorpommern, Northeast Germany (23, 174 km²). Approach Our approach adopts various concepts from modern red listing and prioritization at various organizational levels of biodiversity, and combines them into a methodological framework applicable for regional to continental Red Lists of plant communities. For each distinguished plant community, three steps are carried out, i.e. (1) assessment of endangerment (scientific part, using the three criteria 'past trend', 'current status' and 'prognosis'), (2) assessment of conservation value (normative part, using the three criteria 'degree of naturalness', 'relevance for species conservation' and 'global relevance'), and (3) a combination of (1) and (2) to derive a need for action (conservation prioritization). These steps are all based on the successive aggregation of quantitative criteria via decision matrices, which makes the assessment process transparent, avoids definition gaps and allows easy adjustment of the decision rules. Conclusions Plant community types derived from well‐documented classifications of extensive vegetation‐plot databases in combination with a transparent conservation assessment methodology have great potential in nature conservation and environmental monitoring. We suggest that the presented methodology is an improvement on traditional expert judgments as it separates the scientific and normative parts of the evaluation and uses clear, quantitative criteria and explicit rules to connect these into aggregated measures. It worked effectively and yielded meaningful results for a German federal state. By adjusting the scaling of the criteria, the approach can be adapted, as a whole or in part, to other regions or higher levels of ecosystem typology.